A Framework for Monitoring Ecosystems-Based Adaptation to Climate Change: Experience from The Gambia - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The platform has been fully piloted and is now fully running in the Gambia, though with a few data gaps.